Australian Library Job Advertisements: Seeking Inclusion and Diversity - Thompson, Kim M.; Muir, Rebecca; Qayyum, Asim (Information in Contemporary Society, 2019)
A growing body of literature is drawing our attention to diversity in librarianship, arguing for improved inclusion through better recruitment, retention, and career advancement of minority professionals. While much of the discussion about diversity in libraries is taking place in United States, this article attempts to extend the discussion, bringing attention to diversity and inclusion in Australian librarianship through analysis of Australian library job ads. This article uses content analysis of 96 Australian job ads posted from 22 January to 3 February 2018 in key Australian library job search engines. The analysis focuses on how diversity is reflected in these ads, with a content analysis of wording focused on inviting diversity in terms of ability/disability, ethnicity and language, and gender and sexuality.